2019
DOI: 10.1186/s40425-019-0624-y
|View full text |Cite
|
Sign up to set email alerts
|

Opportunities and challenges of active immunotherapy in dogs with B-cell lymphoma: a 5-year experience in two veterinary oncology centers

Abstract: Background Pet dogs spontaneously develop lymphoma. An anthracycline-based multidrug chemotherapy regimen represents the treatment cornerstone; however, cure is rarely achieved. We have been treating dogs with B-cell lymphoma with an autologous vaccine (APAVAC®) and CHOP-based chemotherapy since 2011. Methods To better characterize the safety and efficacy of APAVAC®, and to find the best candidates for immunotherapy, we designed a retrospective study on all dogs treated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 25 publications
2
25
0
4
Order By: Relevance
“…Overall, compared to dogs treated with chemotherapy only, dogs receiving the chemo-immunotherapy protocol survived significantly longer, regardless of histotype and evaluated prognostic factors. The study also confirmed the excellent tolerability of the vaccine in dogs diagnosed with B-cell lymphomas ( 90 ). Unfortunately, until now there is no information regarding the chemo-immunotherapy treatment response in T-cell lymphoma dogs.…”
Section: Current Immunotherapies For Canine Non-hodgkin's Lymphomasupporting
confidence: 68%
“…Overall, compared to dogs treated with chemotherapy only, dogs receiving the chemo-immunotherapy protocol survived significantly longer, regardless of histotype and evaluated prognostic factors. The study also confirmed the excellent tolerability of the vaccine in dogs diagnosed with B-cell lymphomas ( 90 ). Unfortunately, until now there is no information regarding the chemo-immunotherapy treatment response in T-cell lymphoma dogs.…”
Section: Current Immunotherapies For Canine Non-hodgkin's Lymphomasupporting
confidence: 68%
“…It is not clear if there is a breed-specific predilection for this disease, but several studies of histologically confirmed cDLBCL indicate Golden retrievers, Labrador retrievers, Bernese mountain dogs and German shepherds are commonly affected breeds (10,30,31). Dogs are typically treated with CHOP, with overall survival times varying between studies, from 300 to 500 days (31)(32)(33). Although a number of clinical trials of anti-CD20 therapy in dogs with B cell lymphoma are in progress, to date clinically efficacious antibody therapy is not available for dogs with BCL.…”
Section: Epidemiologymentioning
confidence: 99%
“…Diffuse large B-cell lymphoma (DLBCL) is the most frequent histotype in dogs, accounting for 50–60% of all non-Hodgkin lymphomas [ 1 ]. Despite its relative morphological and phenotypical homogeneity, DLBCL encompasses multiple clinical entities in dogs, and only a small number of animals is definitively cured by treatment [ 1 , 2 , 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%